Breaking the Cycle : A Strategy for Conflict-Sensitive Rural Growth in Burundi - Baghdadli, Ilhem; Harborne, Bernard; Rajadel, Tania (Washington, DC : World Bank, 2012)
The study on the sources of rural growth in Burundi results from a meticulous work carried out by eminent experts of the World Bank in response to a request of the Government of Burundi. It describes the global environment, which explains poverty aggravation and builds proposals to overcome most binding constraints to growth in Burundi. This study is an important contribution in the fight against poverty, as it identifies ways to resume growth in the rural world, which accounts for 90 percent of employment, represents more than 50 percent of gross domestic product (GDP), and over 80 percent of export earnings. Increasing rural income will have large multiplier effects on the national economy. This will enable breaking the vicious circle of poverty and starting a virtuous circle of economic growth and poverty reduction. The study underlines that reforming export-crop sub-sectors such as coffee, tea, and horticulture will help increase participation in higher value specialty markets. Entering these market segments will increase export revenues and producers' incomes.